2003
DOI: 10.5194/acp-3-509-2003
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids as cloud condensation nuclei: Laboratory studies of highly soluble and insoluble species

Abstract: Abstract. The ability of sub-micron-sized organic acid particles to act as cloud condensation nuclei (CCN) has been examined at room temperature using a newly constructed continuous-flow, thermal-gradient diffusion chamber (TGDC). The organic acids studied were: oxalic, malonic, glutaric, oleic and stearic. The CCN properties of the highly soluble acids -oxalic, malonic and glutaric -match very closely Köhler theory predictions which assume full dissolution of the dry particle and a surface tension of the grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(69 citation statements)
references
References 30 publications
6
62
1
Order By: Relevance
“…The O : C values were 1.19 and 1.24, and κ values were 0.20 and 0.21, for IOP1 and 2, respectively ( Table 1). The O : C and κ values are consistent with those of some typical SOA compounds, such as malonic acid, which has an O : C value of 1.33 and a κ value of 0.23 (Kumar et al, 2003), and succinic acid, which has an O : C value of 1 and a κ value of 0.23 (Hori et al, 2003). For the LO-OOA and IEPOX-SOA factors, the hygroscopicities vary between the two IOPs.…”
Section: Hygroscopicity Of Pmf Factors and The Variation Of Organic Hsupporting
confidence: 56%
“…The O : C values were 1.19 and 1.24, and κ values were 0.20 and 0.21, for IOP1 and 2, respectively ( Table 1). The O : C and κ values are consistent with those of some typical SOA compounds, such as malonic acid, which has an O : C value of 1.33 and a κ value of 0.23 (Kumar et al, 2003), and succinic acid, which has an O : C value of 1 and a κ value of 0.23 (Hori et al, 2003). For the LO-OOA and IEPOX-SOA factors, the hygroscopicities vary between the two IOPs.…”
Section: Hygroscopicity Of Pmf Factors and The Variation Of Organic Hsupporting
confidence: 56%
“…This is not unreasonable because HOA is thought to be hydrocarbon-like (Zhang et al, 2005a) and aliphatic in nature, and in general, these types of compounds have not been found to be CCN-active in laboratory experiments (e.g. Pradeep Kumar et al, 2003;Raymond and Pandis, 2002). In addition, ambient measurements of particles at locations in which HOA is high, especially at the smaller sizes, have shown that the organic component does not appear to contribute to the CCN-activity (Cubison et al, 2008;Quinn et al, 2008;Broekhuizen et al, 2006).…”
Section: Degree Of Oxygenation and Hygroscopicity: Assumptions And Apmentioning
confidence: 96%
“…The cooler bottom plate was maintained at room temperature while the warmer upper plate was actively heated with a resistive heating pad (Omega) to the temperature required for the desired supersaturation as calculated and controlled by a Labview (National Instruments) program from the temperature of the cooler bottom plate. Like the chamber described by Pradeep Kumar et al (2003), this instrument has a movable injector that allows the residence time to vary from 9 to 21 s. The residence time of the chamber was adjusted to optimise the CCN concentration, which, for most of this study, occurred at 19 s. This time is a balance between giving the droplets sufficient time to grow to sizes large enough to be counted by the APS and preventing the aerosols from growing so large that they are lost to gravitational settling. The optimal residence time can also depend on the aerosol chemical composition.…”
Section: Ccn Countermentioning
confidence: 99%
See 1 more Smart Citation
“…This typically involves (1) collection of cloudwater followed by offline chemical analysis (e.g. Parungo et al, 1982;Collett et al, 2002;Decesari et al, 2005;Hutchings et al, 2009) or (2) in situ sampling of cloud droplets followed by isolation of these droplets from the interstitial aerosol using a counterflow virtual impactor (CVI), evaporation of water from the droplet, and chemical analysis of the residual (e.g. Ogren et al, 1985;Noone et al, 1988;Heintzenberg et al, 1996;Twohy and Gandrud, 1998;Kamphus et al, 2010).…”
Section: Introductionmentioning
confidence: 99%